Editorial comments/ Redaksionele Kommentaar - T Kluyts (AOSIS, 2005)
The experiences of professional nurses with their managers play an important role in the quality of service rendered by nurses. Opsomming Die ervaringe van professionele verpleegkundiges met hul verpleegbestuurders speel 'n belangrike rol in die gehalte diens gelewer deur verpleegkundiges. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.